Refugee Integration between a Rock and a Hard Place: Challenges and Possibilities of Local Integration as a Durable Solution for Eritrean and Somali Refugees in Ethiopia - Mena, Wogene Berhanu (African Human Mobility Review, 2021)
This study examines the challenges and possibilities of local integration for urban refugees by comparing two refugee groups (Eritreans and Somalis) in Addis Ababa. A qualitative research methodology was employed and semistructured interviews with refugees and host communities as well as key informant interviews with the Administration of Refugees and Returnees Affairs (ARRA) and local authorities were conducted. In addition, focus group discussions (FGDs) with refugees and host communities of the study areas were held. The respondents for both interviews and FGDs were purposively selected. The historical and ongoing relations between Ethiopia and the refugee producing countries, a structural factor, impacted not only the country’s policy direction towards the refugees’ but also the refugees’ and hosts’ perceptions of local integration. The study revealed that Somali refugees are more integrated in the host communities than Eritrean refugees in the respective areas despite the cultural compatibility of the latter because of the interplay of structural, refugee and host community related factors.